From Uniformity towards Unequality in Regional Development Policy: The Case of France - Ildikó Egyed (DETUROPE)
The French national territory is characterised by a rich variety of landscapes and regions upon which the post-revolutionary Jacobin Republic imposed its homogenising territorial administration with the objective of achieving uniformity and a greater transparency. Territorial unity formed the basic pillar of the Republic, which no successive regimes were able to undermine and no peripheral bottom-up regionalisation movements could challenge until the end of the past decade. However, from the second half of the 20th century, the unified national territory was increasingly subject to a „two-speed” development, with declining socio-economic conditions outside the zone of influence of the capital city. Spatial disparities and the fear of the desertification of rural areas due to the generalisation of industrialisation and the rapid extension of the Fordist capitalist accumulation regime constituted the background of the genesis of spatial planning to serve as a counterbalance to spontaneous processes of spatial polarisation.